Being Modern: Minangkabau Women in Two Shortstories of Nasrul Siddik Aia Matonjo and Intan Sinaro Tolong Tjarikan - Yulia, Novi (Faculty of Humanities, Andalas University, Padang, West Sumatra in cooperation with Kato Institute., 2024)
This study delves into the feminist themes in contemporary Minang literature, particularly concerning urbanization and modernization. Specifically, it focuses on two short stories by Minang authors to explore the representation of feminism during the time of writing. Through these works, the authors aim to highlight the issues faced by women in Minangkabau, including limited educational opportunities, societal pressure to marry early, and the pursuit of decision-making autonomy. The discussion of feminist discourse in literature sheds light on the complex relationship between urban and rural influences on gender roles and expectations. Keywords: feminism, representation, Minangkabau, literature piece